Bank Cleanups, Capitalization, and Lending: Evidence from India. (15th October 2020) - Chopra, Yakshup; Subramanian, Krishnamurthy; Tantri, Prasanna L
Abstract: We examine the Indian bank asset quality review, which doubled the declared loan delinquency rate. Relative economic stability during the exercise and the absence of a capital backstop together make it unique. We find that the expected reduction in information asymmetry does not automatically lead to the recapitalization of banks by markets. The consequent undercapitalization leads to underinvestment and risk-shifting through zombie lending. The impact flows to the real economy through borrowers, including shadow banks, and adversely impacts growth. These findings show that bank cleanup exercises not accompanied by policies aimed at recapitalization may be insufficient even during normal times.